PP28 A simulation pilot study: evaluation of the impact on both clinical and non-clinical skills for newly qualified Physician Associates. (10th November 2020) - Torble, Bryony; Schoen, Kimberly; Storey, James
Abstract : Background: Simulation is a mainstay of education in medical training and has been shown to improve academic achievement and teamwork(1). However, it is not yet a core part of the curriculum for Physician Associate (PA) interns at Leeds Teaching Hospitals. Summary of Work: Three simulation scenarios were designed for newly qualified PA's to manage; delirium, acute asthma and hypovolaemic shock. Three delegates participated in each scenario, with one delegate identifying as 'team leader' and the remaining two acting as 'team members'. Two surveys were issued pre and post simulation; an assessment of clinical knowledge and another of confidence levels. A clinical knowledge question pool was created using single best answer questions aimed at final year medical students. Questions were randomly allocated to pre- and post-simulation assessments. Confidence levels were self-reported on a Likert scale in the following domains; performing an A-E assessment, managing an acutely unwell patient and handover. Summary of Results: The majority of participants scored higher in the post-simulation clinical knowledge assessment (mean score of 61.5% pre-simulation versus 70.1% post-simulation (p=0.003)). A non-significant (p>0.05) trend towards improved confidence across all areas was observed. Notably two team leaders reported decreased or unchanged confidence in the post-simulation survey. No team members reported a reduction in confidence post-simulation. Discussion and Conclusions: The impact of simulation based teaching is typically assessed using qualitative measures rather than the quantitative approach assessing clinical knowledge used in our study. Despite the small sample size, it was encouraging that test scores improved after simulation sessions and may indicate that simulation consolidates clinical acumen. Reduced confidence reported by team leaders may be secondary to recognition of their previous unconscious incompetence whilst making clinical decisions. The accelerated nature of PA training and fewer opportunities it provides to manage acutely unwell patients may be a significant contributor. Recommendations: Simulation can be an important tool to improve both clinical knowledge and non-technical skills in newly qualified PA practitioners. Our study reminds us that simulation can have a negative impact on confidence and faculty should be mindful of this when facilitating debrief and reflection. We would like to encourage formal incorporation of simulation training into the curriculum of PA interns. Reference: Lighthall GK, Barr J. The use of clinical simulation systems to train critical care physicians. Journal of Intensive Care Medicine 2007;22(5) :257–269. https://doi.org/10.1177/0885066607304273